CRISPR/Cas9 mediated approach to generate YAP-depleted human embryonic stem cell line (MUSIe002-A-1) - Sujittra Khampang; Nittaya Jiamvoraphong; Chuti Laowtammathron; Chanchao Lorthongpanich; Phatchanat Klaihmon; Pimonwan Srisook; Xing Kang; Sudjit Luanpitpong; Yaowalak U-pratya; Surapol Issaragrisil (Stem Cell Research, 2023)
Yes-associated protein (YAP), an important effector protein of the Hippo signaling pathway, acts as a molecular switch in controlling cell proliferation and apoptosis. In this study, a YAP-targeted isogenic sub-clone of the MUSIe002-A was generated, designated as MUSIe002-A-1. The MUSIe002-1 cell line had normal pluripotent stem cell characteristics and karyotype. Its ability to differentiate into three germ layers was confirmed. As reduction of YAP does not disturb the pluripotency of hESCs, this cell line serves as a valuable model to extrapolate the functional role of YAP in stem cell biology and its applications.